Electrospun poly(ε-caprolactone)/bovine hydroxyapatite (BHA) composite nanofibers for bone tissue engineering - (:unkn) unknown (Trans Tech Publications Ltd, 2017)
Tissue engineering applications have opened a new future-promising era for critical injuries, defects and diseases. Bone tissue engineering is the part of tissue engineering which aims to stir up new practical bone re-formation via the interactive combination of biomaterials and cells. Poly (ε -caprolactone) (PCL) is a unique semi crystalline polymer material, which handles several important features such as biocompatibility, high biomedical durability and degradation properties [1]. Bovine hydroxyapatite (BHA) is another biocompatible material which provides to get ultimate mechanical behavior in composite designs. Because of their high biocompatibility, PCL and BHA were integrated in the electrospinning system together. The system was revised for multi-feeding needle equipment. Eight dissimilar tissue scaffolds were produced and investigated for this recent work. © 2017 Trans Tech Publications.
Keywords: Biopolymers; Electrospinning; Mechanical testing; PCL